Building great health care teams: enhancing interprofessional work readiness skills, knowledge and values for undergraduate health care students. Issue 2 (3rd March 2020) - Venville, Annie; Andrews, Paul
ABSTRACT: Collaborative ways of working have become increasingly important as healthcare adopts a more team-based approach to patient care. Interprofessional education (IPE) addresses some of the challenges associated with collaborative working and is increasingly offered to learners pre and post qualification. This article reports on a three-day IPE program designed to enable undergraduate health professional students develop interprofessional (IP) work readiness skills, knowledge, and values while undertaking clinical placement in a hospital setting. The curriculum built participant skills in culturally safe IP collaboration (IPC); focused on strategies for providing quality care to indigenous peoples and communities, and overtly linked IP competence to organizational mission and values. It highlighted the patient voice and displayed both the human cost of poor team communication and the comfort family members gained from watching united treating teams working with skill, compassion, and kindness. Twenty-four students from seven healthcare disciplines completed the program (N = 24). The Work Self-Efficacy Inventory (WS-Ei) and the Interprofessional Socialization and Valuing Scale (ISVS) assessed participant IP skills, knowledge, beliefs, values, attitudes, and confidence before and after program completion. A paired sample t -test showed an increase in mean scores in all responses on both scales. Results suggest that participation in the IPE program resulted in substantial shifts in knowledge, skills, and values as evidenced by changed assumptions and worldviews, enhanced knowledge and skills concerning IPC, improved understanding of other professional roles and increased confidence in managing workplace experiences.